2018
DOI: 10.1080/02640414.2018.1499392
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular function in elite male athletes meeting the structural echocardiographic task force criteria for arrhythmogenic right ventricular cardiomyopathy

Abstract: Athlete pre-participation screening is focused on detecting pathological conditions like arrhythmogenic right ventricular cardiomyopathy (ARVC). The diagnosis of ARVC is established by applying the revised 2010 ARVC Task Force Criteria (TFC) that assesses RV structure and function. Some athletes may meet structural TFC without having ARVC but we do not know the consequences for RV function. This study compared RV structural and functional indices in male athletes that meet the structural TFC (MTFC) for ARVC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…There is a significant overlap between myocardial RV morphologic alterations described in ARVC and the athlete’s heart [ 5 , 6 , 7 ]. The revised 2010 TFC were developed in order to improve the diagnosis of ARVC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a significant overlap between myocardial RV morphologic alterations described in ARVC and the athlete’s heart [ 5 , 6 , 7 ]. The revised 2010 TFC were developed in order to improve the diagnosis of ARVC.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, observational echocardiographic studies reported contrasting findings for cardiac function and dimensions in athletes compared to ARVC [ 5 , 6 , 7 ]. Data about the physiological exercise-induced alterations involving the right atrium (RA) in athletes compared to patients with ARVC is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the analysis of the data obtained at the first stage of the study, we have reason to believe that the registration of TRP during the Martine test allowed a deeper study of the nature of the central hemodynamic response to DL and describe the physiological picture of hemodynamic response in normotonic response as follows: muscles, in particular, oxygen demand, should be provided by increase in MVB; reduction of vascular resistance of blood flow and increase of pulse blood pressure improve the state of perfusion of the capillary bed of working muscles, and the stability of adBP ensures optimal conditions for metabolism of water, nutrients and other components between blood and tissue fluid [1,3,13,17,21].…”
Section: Discussionmentioning
confidence: 99%
“…Zaidi et al showed that a ratio of ≤0.9 could be used as a parameter to distinguish between physiological remodelling and ARVC (Figure 5A). 24,27,29 …”
Section: Diagnostic Evaluation and Findingsmentioning
confidence: 99%